Evaluation of Padjadjaran Maize Hybrids in intercropping system with soybeans under albasia shade - Yuwariah, Yuyun; Soendajana, Audi Razaqa; Wicaksono, Fiky Yulianto; Ruswandi, Dedi (Kultivasi, 2024)
Intercropping between maize and soybean has been known to be widely practiced by subsistence farmers. Some farmers do intercropping in production forests and there are no scientific data about it. The aims of the study were to evaluate the growth and yield of Padjadjaran maize hybrids and to estimate Land Equivalent Ratio, Competitive Ratio, and Stress Tolerance Index under intercropping of maize and soybeans under the shade of Albasia. The experiment was carried out from January to June 2021 in Tanjungsari, Sumedang Regency with an altitude of 818 m above sea level. The experiment used a Randomized Block Design (RBD) which consisted of 21 treatments of Padjadjaran maize hybrids intercropped with soybeans and with three replications. For control, soybean and maize has planted by using monocropping simultaneously. The experimental results showed that hybrids of MDR 3.1.2 x MDR 153.14.1, BR 154 x MDR 153.3.2, and DR 4 x MDR 7.2.3 gave the best growth and yield components under intercropping system with soybeans. However, the other Padjadjaran hybrids gave better Land Equivalent Ratio, Competitive Ratio, and Stress Tolerance Index.